Divergence of functions and expression patterns of soybean bZIP transcription factors - Yue, Lin; Pei, Xinxin; Kong, Fanjiang; Zhao, Lin; Lin, Xiaoya (Frontiers in Plant Science, 2023)
Soybean (Glycine max) is a major protein and oil crop. Soybean basic region/leucine zipper (bZIP) transcription factors are involved in many regulatory pathways, including yield, stress responses, environmental signaling, and carbon-nitrogen balance. Here, we discuss the members of the soybean bZIP family and their classification: 161 members have been identified and clustered into 13 groups. Our review of the transcriptional regulation and functions of soybean bZIP members provides important information for future study of bZIP transcription factors and genetic resources for soybean breeding.